FRI0032 Curative effect of camellia sinensis (CS) against opportunistic infection in vulnerable animal model of rheumatoid arthritis. (15th June 2017) - Tanwar, A; Chawla, R; Basu, M; Arora, R; Khan, HA
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease characterised by chronic inflammation of pro-inflammatory cytokines. Opportunistic infection plays a significant role in loss of tolerance to citrullinated proteins along with inflammatory progression of RA. Due to the immunosuppressive property of anti-rheumatic drugs, the patients of RA become highly vulnerable to microbial infections [1]. Thus, the present study employed an in vivo animal model to explore the holistic remedies for the effective treatment of RA. Objectives: To study the immunomodulatory effect of Camellia sinensis (Cs) against inflammatory disorder Methods: Study utilized collagen induced arthritis (CIA) rat model with Salmonella typhimurium (10 8 CFU/ml, p.o) as an opportunistic infectious agent which was introduced to enhance disease severity (on 21st day)[2]. Treatment with Cs at oral dose 400 mg/kg/body wt. (p.o) was started from 21st day for 14 days to explore its curative, anti-edematogenic effect and quantitation of oxidative stress markers. To validate biochemical changes, the histopathologiy and level of cytokines were also studied in joint tissue followed by 7 Tesla Magnetic Resonance Imaging (7T MRI). Results: Treatment groups significantly restored the level of oxidative stress markers (Table-1). Furthermore, there was significant reduction in the number of bacterial colonies in blood and fecal matter in the treatment group as compared to infected group, while pro-inflammatory cytokine level of TNF-α, IL-1, IL-6 was significantly lower in joint tissue. Histological & 7T-MRI changes in the treatment group included significant reduction of cartilage erosion & pannus formation and there were no signs of inflammation in the small intestine as compared to arthritic and infected group (Figure 1 ). Conclusions: The present study demonstrated that Cs has anti-inflammatory effect and could also be used as potent immunomodulator to manage RA. References: R. Fleischmann, et al, Efficacy and safety of tofacitinib in patients with active rheumatoid arthritis: review of key Phase 2 studies, Int. J. Rheum. Dis. (2016). doi:10.1111/1756–185X.12901. D.D. Brand, et al Rosloniec, Collagen-induced arthritis, Nat. Protoc. 2 (2007) 1269–1275. doi:10.1038/nprot.2007.173. Acknowledgements: Authors are greatful to VC, Jamia Hamdard and Director, INMAS for providing research facility and support. Disclosure of Interest: None declared